Tingkat Kelayakan Jalur Pedestrian di Jalan KH. Abul Hasan, Kota Samarinda - Nava Chairunisa Nabila; Rizky Arif Nugroho; Arief Hidayat; Rulliannor Syah Putra (COMPACT: Spatial Development Journal, 2023)
Based on the RTRW (Regional Spatial Planning) in Samarinda City for the period 2014 to 2034 it states that there are plans for urban infrastructure on Jalan KH. Abul Hasan, namely in the form of providing and using pedestrian network infrastructure facilities in the Samarinda City area. However, in reality, the pedestrian paths in the area do not meet the criteria set for road users. The purpose of this study was to analyze the feasibility level of pedestrian paths for pedestrian path users by analyzing the Pedestrian Environmental Quality Index (PEQI). Quantitative qualitative descriptive analysis method based on PEQI analysis from direct observation with traffic indicator variables, pedestrian path design, and use of pedestrian path space with nine sub-variables contained therein. Jalan KH. Abul Hasan, City of Samarinda in this study is divided into three segments based on building designation, namely Segment 1 (Trade and Services), Segment 2 (Education), and Segment 3 (Green Open Space). The results of the PEQI in the three segments are the quality of basic pedestrian paths, which have standard or average (basic) quality provided conditions are met, but can be improved (III).